Innovative thinking in the leaders and competitiveness of SMEs in the Industrial sector in Colombia (2022)
At a global level, it is thought that organizations, which carry out innovation, are more competitive in the market and achieve a greater competitive advantage; The objective of this scientific article is to identify if innovative thinking in managers influences the competitiveness of SMEs. Currently, most research on innovation has not explored its relationship with the innovative thinking of leaders; the literature is unclear as to what innovative companies do differently to achieve superior performance. This study advances in the investigation of how the mentality of leaders influences innovation processes, for this purpose the difficulties faced by SMEs in the industrial sector in Colombia were analyzed, finding that at the country level it is not clear that there is a culture of innovative thinking in their leaders. The research was carried out under the descriptive approach, supported by qualitative and quantitative studies of a sample of Colombian SMEs. The research is associated with the analysis of data on competitiveness, innovation, and technological development in SMEs; in Colombia, the highest concentration of researchers is in the education sector with 95.7% and only 2.5% is in companies, 1.7% is outside the country. In terms of limitations, we found no evidence from studies that promote innovative thinking techniques. The practical implications of this research are to demonstrate the importance for SMEs of strengthening research in their managers and teams to generate innovation; the originality or value of this document is in promoting a model for the development of innovative thinking in leaders.